The Roads of Intersubjectivity - Silva, Anderson Aparecido Lima da (Primeiros Escritos, 2009)
Reviewing the “modern theories”, Sartre wants to stablish an understanding of the intersubjectivity placed not in an epistemological plan, but in the plan of the existence. This way, entering the To-self’s (Pour-soi) cotidian life, show ups the being-other thay he is by the reciprocity of a double constitutive relation with the other subjects in their active position. Sartre emphasizes the interdependence and the conflicts of the relation I/Other. To conclude, we will show the radical freedom as the source of this relation. The Look’s dialetic will be the reference point of our exposition’s development